Teaching experience: challenges to deal with the current generation of higher educational students - Candido, Rodrigo Medici; Gomes, Maurici Dias; Domingos, Ricardo Augusto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper presents a qualitative analysis basic interpretative, with the aim to analyze the teacher´s experience face the change of student´s generation of higher education. Six open face semi-structured interviews were conducted with professionals, there are at least 10 years in higher education and currently employed. The results indicated a universalization of higher education, a constantly growth of students and a behavioral change on the current generation of students. One of the main factors for this phenomenon lies in the technology, which represents a benefit to the student and a challenge to the teacher, who needs constantly to update and improve their classes, with the inclusion of updated content.